ADAPTIVE CONTROL SYSTEM OF INDUSTRIAL REACTORS - Vyacheslav K. Mayevski (Статистика и экономика)
This paper describes a mathematical model of an industrial chemical reactor for production of synthetic rubber. During reactor operation the model parameters vary considerably. To create a control algorithm performed transformation of mathematical model of the reactor in order to obtain a dependency that can be used to determine the model parameters are changing during reactor operation.